Bayesian Model Averaging Approach of the Determinants of Foreign Direct Investment in Morocco - Arbia, Anass; Sobhi, Khalid; Karim, Mohamed; Chtioui, Nor-Eddine; Hoummad , Rachid (International Journal of Economics and Financial Issues, 2025)
Historically, research on foreign direct investment (FDI) was based mainly on Dunning’s Ownership-Location-Internalisation (OLI) paradigm. However, the emergence of digitalisation has highlighted the key role of information and communication technologies (ICTs), while globalisation has underscored the importance of political and social institutions in promoting foreign investment. Beyond location advantages, traditionally focused on macroeconomic aspects, it has become essential to integrate the digital, institutional, and financial dimensions to better understand the determinants of FDI. This study therefore sets out to identify the main factors influencing FDI in Morocco, incorporating recent advances in digitalisation and globalisation. To address the diversity of potential factors influencing FDI, the Bayesian model averaging (BMA) approach was adopted to reduce the uncertainty associated with the choice of variables. A model integrating the technological, economic, institutional, and financial dimensions (ICT-E-I-F) was thus developed for the period 1995Q1–2023Q4.The empirical evidence reveals that trade openness (PIP = 1.00), human capital (PIP = 1.00), and macroeconomic stability (PIP = 1.00) have a highly significant influence on FDI. Conversely, factors such as taxation (PIP = 0.96) have a moderate impact. Additionally, other factors, such as fixed telephone subscriptions (PIP = 0.80), GDP growth (PIP = 0.63), GDP per capita (PIP = 0.52), and the financial market size (PIP = 0.52), exhibit a weakly significant impact on FDI.